(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the relevance of studying the current state, amount, quality and quantitative indicators of juvenile delinquency in the Prevention of major causes and offenses that cause changes. Juvenile delinquency is a major threat to society. Adolescents are a reserve for crime, as many have begun this path at an early age, while continuing criminal activities such as adults. In order to effectively combat and prevent this type of crime, it is necessary to study criminological indicators. It is necessary to identify preventive measures and develop the necessary measures to influence the personality of minor offenders, to study quantitative and qualitative indicators. The number of crimes committed by minors has increased by 29.4 percent over the past three years. In conclusion, the General Dynamics and level of juvenile delinquency has been increasing from 2020 to June 2023, as well as the fact that the crimes are severe, acute, according to their nature and level of social danger, the amount of crimes committed in the group has not decreased. So it was found that there are negative changes in the indicators of the state and dynamics of juvenile delinquency.